Tetrazygia bicolor Florida Tetrazygia, West Indian Lilac - Edward Gilman (EDIS, 2007)
This document provides an overview of Taxus floridana, commonly known as Florida yew. It describes the plant’s characteristics, including its slow growth, dense foliage, and soft, dark green needles. The plant produces insignificant flowers and small, red, pulpy fruits that are poisonous. Florida yew is noted for its use as a specimen, hedge, or foundation planting due to its compact growth and ornamental features. The document also covers the plant’s propagation methods, pest resistance, and cultural needs, emphasizing its suitability for planting in USDA hardiness zones 8 through 9A. Original publication date October 1999.